2015
DOI: 10.1111/jam.12845
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of organic acids and salt depending on type of acids and pathogens in laboratory media and acidified pickle

Abstract: This study shows that antagonistic effects were observed when Gram-negative bacteria were treated with organic acids of simple structure. It may provide useful information for understanding the acid resistance mechanism of Gram-negative bacteria and developing methods for preserving acidified food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…ECAA and ECSA exhibited similar survival trends during fermentation and storage. Previous studies indicated a cross protective effect of ATR with acid adaptation leading to increased salt resistance (Bae & Lee, ; Lee & Kang, ). This may explain similar survival rates for ECAA and ECSA.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…ECAA and ECSA exhibited similar survival trends during fermentation and storage. Previous studies indicated a cross protective effect of ATR with acid adaptation leading to increased salt resistance (Bae & Lee, ; Lee & Kang, ). This may explain similar survival rates for ECAA and ECSA.…”
Section: Resultsmentioning
confidence: 92%
“…However, ECSA increased by 1 log during fermentation only in cheeses containing 4% salt. Acid production by the starter culture helps to prevent the growth of increased salt resistance (Bae & Lee, 2015;Lee & Kang, 2009). This may explain similar survival rates for ECAA and ECSA.…”
Section: Chemical Composition and Textural Properties Of The Cheesementioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, such a protective phenomenon is not observed when bacteria were cultivated on media containing HCl. Bae and Lee () also reported a protective effect of salt on the survival of E. coli O157:H7 during treatment with acetic, lactic, or propionic acid in TYE broth. A similar result was obtained by Casey and Condon () as well.…”
Section: Discussionmentioning
confidence: 92%
“…Similar results were reported by Hosein et al (2011), who demonstrated a protective effect of salt on the cell survival at a controlled concentration of acetic acid. According to a study conducted by Bae and Lee (2015), these authors showed that the addition of salt stress increases the resistance of Gram-negative bacteria to acid stress when acetic, lactic, or propionic acid is used. In particular, Escherichia coli 2010).…”
Section: Introductionmentioning
confidence: 99%